"The Whole Is Greater Than the Sum of the Parts": Prison Staff Perceptions of Domestic Violence Rehabilitation Programs - Shoham, Efrat (International journal of offender therapy and comparative criminology, 2018)
This qualitative study is part of a mixed methods research project that examined the effectiveness of the primary rehabilitation program for domestic violence offenders in the Israeli Prison Services—the "House of Hope." The quantitative part of the study showed that the "House of Hope" program was effective in reducing recidivism among participating inmates. The purpose of this qualitative study was to describe the rehabilitation program according to the perspectives of the program staff. For this purpose, semistructured interviews were conducted with the department staff during the study as well as with past directors. The qualitative findings suggested that the success of the program probably stemmed from a synergistic combination of several components, for example, identifying the characteristics of domestic violence offenders and adjusting treatment programs to their needs, along with exposure to psychological treatment in varied therapies (cognitive behavioral therapy, psychoeducational, and psychodynamic) and formats (group therapy and individual therapy) during a 1-year stay in a hierarchical therapeutic community. Other components mentioned are staff professionalism, stability, and the program's location in a therapeutic-oriented prison that is architecturally designed and built to create a less stressful environment for the inmates and the staff.